Interest of Fluvoxamine as an Add-On to Clozapine in Children With Severe Psychiatric Disorder According to CYP Polymorphisms: Experience From a Case Series - Berel, Camille; Mossé, Ulysse; Wils, Julien; Cousin, Lauriane; Imbert, Laurent; Gerardin, Priscille; Chaumette, Boris; Lamoureux, Fabien; Ferrafiat, Vladimir (Frontiers in Psychiatry, 2021)
Despite its drastic efficacy in resistant psychiatric disorders, clozapine remains rarely used in youth due to its side effects. Clozapine plasma level is determined through its metabolism involving several isoforms of cytochromes 450 (CYP450) family. Isoform CYP1A2 appears as a limiting enzyme involved in the metabolism of clozapine, while isoforms 2C19, 2D6, 3A4, and 3A5 also contribute in a minor way. Clozapine efficacy is limited by a significant inter-patient variability in exposure according to CYP's polymorphisms. Clozapine plasma levels may be increased with CYP inhibitors such as fluvoxamine. This drug is a potent enzymatic inhibitor of CYP1A2 and, to a lesser extent, of CYP3A4 and CYP2D6. Hence, in case of CYP's polymorphisms in youth, the use of fluvoxamine as add-on to clozapine could help in reaching clinical and biological efficacy and allowing lower clozapine dosage and a better tolerance profile as it has already been described in adults. We report four pediatric cases with severe psychiatric disorders underlying our experience with CYP polymorphism explorations and the use of fluvoxamine as add-on to clozapine. Our four patients clinically improved after the introduction of fluvoxamine, enhancing clozapine metabolism and therefore the clozapine plasma level within therapeutic range. Despite the interesting results of fluvoxamine, we report a severe issue of tolerance for one patient, emphasizing the need for caution regarding possible drug interactions when fluvoxamine is considered. Hence, we propose a detailed step-by-step multidisciplinary protocol.